Comparison of team and individual results of the young mathematicians competition - Kanišauskienė, Karolina (Lietuvos matematikos rinkinys, 2025)
The article presents a comparative analysis of the team and individual results of the 11th–12th grade students who participated in the Young Mathematicians Competition held between 2022 and 2025, taking into account the solvability of tasks.
Keywords: mathematics olympiad; difficulty; equality of means